Analisis Kualitatif Kelengkapan dan Kekonsistensian Diagnosis di Rumah Sakit Patria IKKT - Suciyanti Suciyanti; Lily Widjaja; Puteri Fannya; Dina Sonia (Yayasan Literasi Sains Indonesia, 2023)
Qualitative analysis is a review of filling in medical records related to the consistency of the contents of medical records. A good medical record must contain complete medical records. This type of research is descriptive with a qualitative approach with observation and interview data collection techniques. This qualitative analysis has 6 components. The purpose of this study was to find out a qualitative analysis of the completeness and consistency of diagnosis in dengue fever patients for the period September-October 2022. This research was conducted using a systematic random sampling method. From 85 medical records, the results of a qualitative analysis on the completeness of the consistency of the diagnosis obtained the percentage of consistency of 63.53%. While the results of the 6 subcomponents include: Completeness of diagnosis at admission: 58.82% incomplete, Consistency of diagnosis at admission: 58.82%, Completeness of diagnosis while being treated: 64.71%, Consistency of diagnosis while being treated amounted to: 64.71%, Completeness of diagnosis when going home amounted to: 67.06%, Consistency of diagnosis when going home amounted to: 67.06%. Of the 6 sub-components the highest proportion of consistency was consistency of completeness and consistency of diagnosis at the time of going home = 67.06%. While the lowest completeness & consistency of diagnosis at admission = 58.82%. The conclusion is that the qualitative analysis of the completeness and consistency of the diagnosis is not 100% in accordance with the Hospital MSS.